Thermodynamics of the CO2 absorption in BaCeO3 and SrCeO3 using thermogravimetric and differential thermal analyses. (January 2019) - Niwa, Eiki; Kondo, Kaori; Aoki, Masatake; Sato, Ryuhei; Yoshizawa, Ryo; Fujishiro, Fumito; Yashima, Masatomo; Hashimoto, Takuya
Graphical abstract: Highlights: SrCeO3 and BaCeO3 were evaluated as CO2 absorbent by TG-DTA under controlled P (CO2 ). CO2 absorption and desorption of SrCeO3 were reversible regardless of P (CO2 ). Equilibrium temperature of AeCO3 +CeO2 ↔AeCeO3 +CO2 decreases with decreasing P (CO2 ). Δ G ° for CO2 absorption reaction was estimated and Ellingham diagram was prepared. The temperature range of CO2 absorption of SrCeO3 was wider than that of BaCeO3 . Abstract: The reaction mechanism of Ae CeO3 ( Ae : Sr, Ba) with CO2 and its thermodynamics were investigated using scanning-type thermogravimetric/differential thermal analysis, TG-DTA, at different CO2 partial pressures, P (CO2 ), to estimate their potential as CO2 absorbents. The standard Gibbs free energy change, Δ G ° of SrCeO3 +CO2 ↔ SrCO3 +CeO2 and BaCeO3 +CO2 ↔ BaCO3 +CeO2 were estimated from equilibrium temperature obtained by the thermogravimetric analyses at different P (CO2 ). From an Ellingham diagram, the standard entropy change, Δ S °, and standard enthalpy change, Δ H °, of each reaction were determined. The obtained Δ S ° and Δ H ° values of the former reaction showed fair agreement with the thermodynamic calculation, whereas those of the latter reaction showed discrepancies from those of the thermodynamic calculations. The Ellingham diagram also suggested that SrCeO3 was superior to BaCeO3 as a CO2 absorbent because the temperature region of SrCeO3 for which the absorption reaction occurred was higher than that for BaCeO3 at constant P (CO2 ).